Flu-like syndromes among the population of the municipality of Barreirinhas, Maranhão, in times of Covid-19 pandemic (Research, Society and Development, 2020)
The present study aimed to know the flu-like symptoms presented by the residents of the municipality of Barreirinhas, state of Maranhão, between the months of March to June 2020. The target audience of this study were 265 people residing in the municipality of Barreirinhas. The survey applied online questionnaires (Google Forms), where questions were asked about the flu symptoms presented by the participants. The present study verified the occurrence of 26 flu-like symptoms among the population of Barreirinhas, of which 22 were the same manifested by people affected by Covid-19. The methodology applied in this study was an adaptation of the National Household Sample Survey - PNAD Covid-19 (2020), from the Brazilian Institute of Geography and Statistics. The results of this analysis showed that the symptoms presented by the study participants were fever, headache, nasal congestion, pain in the eyes, loss of smell and taste, sore throat, difficulty breathing, fatigue, muscle pain, among other clinical manifestations. The data also showed that the duration of reported symptoms, in the vast majority of cases, was 8 to 15 days, and the period that most concentrated reports of flu-like syndromes was May. Based on the information presented, health authorities are recommended to carry out mass testing among the population of Barreirinhas, in order to find out whether these signs manifested during the public health crisis are linked or not to Sars-Cov-2.